29 HUMAN BONE MARROW DERIVED MESENCHYMAL STEM CELLS MEDIATE IMMUNOSUPPRESSION IN EXPERIMENTAL CROHN'S DISEASE BY SECRETING PROSTAGLANDIN E2 AND REPROGRAMMING MACROPHAGES TO AN ANTI-INFLAMMATORY PHENOTYPE. (7th February 2019) - Dave, Maneesh; Zhao, Nan; Mahabaleshwar, Ganapati; Somosa, Rodrigues; Kenyon, Jonathan; Caplan, Arnold; Cominelli, Fabio
Abstract: Background: Locally injected mesenchymal stem cells (MSCs) are now an approved therapy in European Union for perianal Crohn's disease (CD) fistulas, however, clinical studies have shown limited efficacy of systemic MSC therapy for luminal CD. Thus, we studied the SAMP-1/YitFc (SAMP), a chronic and spontaneous murine model of small intestine (SI) inflammation for treatment with human bone marrow derived MSC (hMSC). We previously reported that hMSCs injected intraperitoneally (i.p) into SAMP resulted in histologic, mucosal and radiologic healing (Dave M et al . Gastroenterology 154 (6), S-438). Aims and Methods: The aim of this study was to determine the mechanism(s) by which hMSCs mediate immunosuppression in SAMP. hMSCs were transduced with lentivirus vector containing shRNA for COX-2 (hMSCshCOX-2) to knockdown secretion of Prostaglandin E2 (PGE2 ) and lentivirus with scrambled shRNA was used as control (hMSC-S control). Results: Using NanoString immune cell profiling assay, SAMP mice treated with hMSC i.p had increased abundance of macrophages and decreased abundance of lymphocytes in the SI. In MLRs set up with T lymphocytes from SAMP mice, hMSCs profoundly suppressed T cell proliferation in a dose dependent manner as measured by [ 3 H] thymidine incorporation (95% CI of difference: 8, 573 – 14, 335 cpm; ANOVA P <0.0001 for 2X10 5 hMSCs). By enzyme immunoassay we determined that hMSCs basally secrete PGE2 (4850 ± 86 pg/mL per 100, 000 cells). Indomethacin, a COX-1/2 inhibitor (10 μM) abrogated the suppression of T cell proliferation in MLR and MLR performed with PGE2 inhibited hMSC (hMSCshCOX-2) in comparison to hMSC-S control again demonstrated abrogation of suppression of T cell proliferation (95% CI of difference: 3, 885 – 10, 456 cpm; ANOVA P <0.001 for hMSC-S control and 95% CI of difference: -1, 859 – 7580 cpm; ANOVA P not sig. for hMSCshCOX-2). In co-culture assay hMSCs reprogrammed SAMP macrophages (MØ) to anti-inflammatory phenotype with higher gene expression of arginase I (28.9 fold increase, P <0.0001) and lower gene expression of proinflammatory IL-6 (0.2-fold decrease, P <0.0001), TNF-α (0.2-fold decrease, P <0.0001), IL-1α (0.3-fold decrease, P <0.0001), and IL-1β (0.4-fold decrease, P <0.0001) compared to untreated SAMP MØ. The supernatants from MØ co-cultured with hMSCs contained higher amounts of PGE2 than MØ alone (4100 ± 394 pg/mL vs.81.6 ± 70.7 pg/mL; P <0.001). Flow sorting for C11b+ and F4/80+ MØ four weeks after treatment, demonstrated that MØ from SAMP mice treated with i.p hMSC had an anti-inflammatory phenotype characterized by higher gene expression of arginase-I (13.6-fold increase, P =.01, n=8) and lower gene expression of TNF-α (0.76-fold decrease, P =0.1, n=8) compared to untreated mice. Conclusion: hMSCs mediate immunosuppression by secreting PGE2 and reprogramming macrophages to anti-inflammatory phenotype in SAMP model of experimental CD.